The Role of Chemistry in The Fourth Industrial Revolution - I Wayan Muderawan (Prosiding Seminar Nasional MIPA, 2018)
The Fourth Industrial Revolution is building on the digital revolution that characterized by a fusion of technologies that is blurring the lines between the physical, digital, and biological spheres. Those technologies strongly depend on smart materials or advanced material chemistry. Chemistry known as the central science is a science that studies the composition, structure, and properties of materials and the changes that materials undergo. Chemistry, especially Advanced Materials Chemistry, played a leading role in previous industrial revolutions, through its research, innovations and products. Today, advanced material chemistry is an important enabler of the Fourth Industrial Revolution through its discoveries and innovations of new smart materials. Smart materials are defined as materials that sense and react to environmental conditions or stimuli, such as conducting polymers for OLEDs, optical fibers for transmitting light used in communication technology, and carbon nanotubes for nanochips technology. Those materials are essential building block for digital technology. Its contributions allow other fields of sciences to turn ideas, research, and innovations into sophisticated products supporting digital transformation. On the other hand, chemistry industry itself is also being transformed through digitalization. Digitalization helps increase productivity and safety across the industry’s value chain and supports the design of new offerings. Further, the industry needs to closely monitor pockets of digital disruption.Keywords: chemistry, material chemistry, smart materials, industrial revolution 4.0